The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/02640414.2015.1075055
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods to determine bilateral asymmetries in vertical leg stiffness

Abstract: Whilst the measurement and quantification of vertical leg stiffness (K vert ) asymmetry is of important practical relevance to athletic performance, literature investigating bilateral asymmetry in K vert is limited. Moreover, how the type of task used to assess K vert may affect the expression of asymmetry has not been properly determined. Twelve healthy males performed three types of performance tasks on a dual force plate system to determine K vert asymmetries; the tasks were (a) bilateral hopping, (b) bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 27 publications
5
79
1
Order By: Relevance
“…Despite the magnitude of the difference in vertical stiffness between the fast and slow groups, differences in vertical ground reaction force and centre of mass displacement were not significant and only the former was associated with a 'moderate' effect size. This is not in agreement with a previous findings which identify centre of mass displacement as a strong factor in determining vertical stiffness asymmetry (Maloney et al, 2015), although it should be noted that the current study expressed vertical ground reaction force relative to body mass whereas the previous investigation analysed raw values.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite the magnitude of the difference in vertical stiffness between the fast and slow groups, differences in vertical ground reaction force and centre of mass displacement were not significant and only the former was associated with a 'moderate' effect size. This is not in agreement with a previous findings which identify centre of mass displacement as a strong factor in determining vertical stiffness asymmetry (Maloney et al, 2015), although it should be noted that the current study expressed vertical ground reaction force relative to body mass whereas the previous investigation analysed raw values.…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, it is likely that asymmetries in both factors have an additive effect that is exhibited in vertical stiffness asymmetry (Maloney et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative whole‐body power was calculated as the external work done per unit time in an attempt to bring the body to a resting state. While many studies have calculated stiffness from initial contact to peak vertical ground reaction force, the authors felt the eccentric phase more useful given that the timing of peak vertical ground reaction force varied considerably (mean ± SD: 41.3 ± 12.0% of total ground contact), with 33% of all participants producing their peak force during the whole‐body concentric phase. When examining the moment‐angle waveforms of the hurdle hop task in this present study, not all joints demonstrated a clear biphasic pattern as presented in previous research .…”
Section: Methodsmentioning
confidence: 99%
“…The notion of inter-limb asymmetries refers to the function of one limb in respect to the other and has been a popular source of investigation in recent years. The majority of literature has focused on the prevalence of between-limb differences in multiple testing modalities such as isokinetic dynamometry (14,37), isometric squat or mid-thigh pulls (16,19), back squatting (30,38), and a variety of jumping-based tasks (3,12,27,28). All of the aforementioned methods have been shown to be sensitive when identifying differences between limbs in both athlete and non-athlete populations.…”
Section: Introductionmentioning
confidence: 99%